PENGARUH KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUASAN KONSUMEN DI SEKAR ARUM FRUITS - Noveli dwi arfinda sari; Denok Mugi Hidayanti; Riza Wahyu Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of product quality and service quality on customer satisfaction at Sekar Arum Fruits. The background of the research lies in the importance of maintaining customer satisfaction within the fresh fruit retail sector amid increasingly competitive business conditions. A quantitative approach was employed using descriptive and causal methods. The sample consisted of 96 respondents selected through purposive sampling. Data were collected using a validated and reliable questionnaire. The analysis was conducted using multiple linear regression with the assistance of SPSS. The findings show that neither product quality nor service quality has a significant effect on customer satisfaction, either partially or simultaneously. This is indicated by significance values greater than 0.05 in both the t-test and F-test. The R square value of 0.001 reveals that only 0.1% of the variation in customer satisfaction is explained by the two independent variables, with the remainder influenced by other unexamined factors. These results imply that in the context of Sekar Arum Fruits, factors such as price, store convenience, and promotional strategies may play a more dominant role in shaping customer satisfaction.